1993
DOI: 10.1172/jci116382
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil cationic granule proteins impair thrombomodulin function. A potential mechanism for thromboembolism in hypereosinophilic heart disease.

Abstract: Thromboembolism is a prominent but poorly understood feature of eosinophilic, or Loeffler's, endocarditis. Eosinophil (EO) specific granule proteins, in particular major basic protein (MBP), accumulate on endocardial surfaces in the course of this disease. We hypothesized that these unusually cationic proteins promote thrombosis by binding to the anionic endothelial protein thrombomodulin (TM) and impairing its anticoagulant activities. We find that MBP potently (IC5, of 1-2 gM) inhibits the capacity of endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
97
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(101 citation statements)
references
References 47 publications
0
97
0
4
Order By: Relevance
“…In addition, major basic protein or eosinophil cationic protein, which is an eosinophil granule protein, activates platelets and promotes thrombus formation by inhibiting the function of thrombomodulin in hypereosinophic syndrome or allergic disease. 16,17 Rohrbach et al 18 reported that major basic protein and eosinophilic peroxidase activate platelets. Emanuele et al 19 suggested that increased eotaxin levels, an eosinophil-specific chemoattractant, are associated with the presence of coronary artery disease and that circulating levels of this chemokine may reflect the extent of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, major basic protein or eosinophil cationic protein, which is an eosinophil granule protein, activates platelets and promotes thrombus formation by inhibiting the function of thrombomodulin in hypereosinophic syndrome or allergic disease. 16,17 Rohrbach et al 18 reported that major basic protein and eosinophilic peroxidase activate platelets. Emanuele et al 19 suggested that increased eotaxin levels, an eosinophil-specific chemoattractant, are associated with the presence of coronary artery disease and that circulating levels of this chemokine may reflect the extent of coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The existence of these anionic domains has prompted interest in potential interactions of cationic compounds with the TM/protein C system. Polybrene 6 and the cationic polypeptides polylysine, 9 eosinophil major basic protein, 10 and eosinophil peroxidase 10 all strongly inhibit both the proteolytic conversion of protein C to APC by the thrombin/TM complex (ie, the protein C-activating cofactor activity of TM) and the ability of TM to prolong the thrombin clotting time (ie, the "direct anticoagulant" action of TM). Thus, these cationic proteins impair the anticoagulant functions of TM and may therefore produce a thrombotic phenotype in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[13][14][15][16] In addition, major basic protein or eosinophilic cationic protein, which is an eosinophil granule protein, activates platelets and promotes thrombus formation by inhibiting the function of thrombomodulin in hypereosinophilic syndrome or allergic diseases. 8,9) Rohrbach et al 7) reported that major basic protein and eosinophil peroxidase activate platelets. In the present study, eosinophils were most frequently observed near the boundary of white thrombus and red thrombus, which develops after white thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…3,6) In addition, granule proteins of eosinophils may also promote thrombus formation and growth. [7][8][9] The recent development of thrombus aspiration therapy has allowed for the investigation of thrombi and atheroma fragments. However, histologic evaluation of inflammatory cells involved in ACS has not been sufficiently thorough.…”
mentioning
confidence: 99%